Regional Demographic Correlates of Aggregate Readiness for Sustainable Entrepreneurship in the Wielkopolska Region in Poland, 2016 to 2025 - Kwaśniewski, Jacek Piotr (Journal of Emerging Markets and Management, 2026)
This article aims to analyze the regional demographic correlates of overall readiness for sustainable entrepreneurship. The study aims to identify the impact of age and gender structure on the declared willingness to conduct business activities consistent with the principles of sustainable development in the Wielkopolska region in Poland between 2016 and 2025. The analysis is macroeconomic and ecological in nature, based on aggregated survey data and regional demographic data. The analysis does not identify determinants at the individual level, and the obtained relationships should be interpreted as ecological correlations. The results indicate that the age and gender structure in the region correlates with changes in overall readiness for sustainable entrepreneurship, with the participation of younger working-age cohorts being particularly significant. The dependent variable is the average annual level of readiness for sustainable entrepreneurship (SEE), constructed based on surveys conducted among entrepreneurs. The study utilized statistical and econometric methods, particularly the classical least squares method, and calculations were performed using the GRETL package. The results of the analyses indicate statistically significant correlations between the region’s demographic structure and the level of readiness to implement sustainable development principles in business. A particularly strong and positive effect was noted for men under 40, suggesting greater openness to ecological and social innovations in this group. At the same time, negative correlations were observed for older age cohorts and the overall population, which may be due to structural and competitive factors. The author emphasizes the exploratory nature of the model and the limitations resulting from the ecological level of analysis, pointing to the need for further research using a multilevel approach.